Hip fractures in a city in Northern Norway over 15 years : time trends, seasonal variation and mortality The Harstad Injury Prevention Study - Emaus, Nina; Olsen, Lena Ringstad; Ahmed, Luai A.; Balteskard, Lise; Jacobsen, Bjarne Koster; Magnus, Trine; Ytterstad, Børge (Osteoporosis International, 2011)
Introduction The aim of the present population-based study was to describe age- and sex-specific incidence of hip fractures in a Northern Norwegian city, compare rates with the Norwegian capital Oslo, describe time trends in hip fracture incidence, place of injury, seasonal variation and compare mortality after hip fracture between women and men. Methods Data on hip fractures from 1994 to 2008 in women and men aged 50 years and above were obtained from the Harstad Injury Registry. Results There were altogether 603 hip fractures in Harstad between 1994 and 2008. The annual incidenc rose exponentially from 5.8 to 349.2 per 10,000 in men, and from 8.7 to 582.2 per 10,000 in women from the age group 50–54 to 90+ years. The age-adjusted incidence rates were 101.0 and 37.4 in women and men, respectively, compared to 118.0 in women (p=0.005) and 44.0 in men (p=0.09) in Oslo. The age-adjusted incidence rates did not increase between 1994–1996 and 2006–2008. The majority of hip fractures occurred indoors and seasonal variation was significant in fractures occurring outdoors only. After adjusting for age at hip fracture, mortality after fracture was higher in men than in women 3, 6 and 12 months (p≤0.002) after fracture. Conclusions There are regional differences in hip fracture incidence that cannot be explained by a north–south gradient in Norway. Preventive strategies must be targeted to indoor areas throughout the year and to outdoor areas in winter.